Geographical Variations in Moringa Oleifera and Its Potential for Stunting Intervention: A Systematic Review - Ika Muryasari; Melyana Nurul Widyawati; Kurnianingsih Kurnianingsih; Nita Aquarista (Indonesian Journal of Global Health Research, 2025)
Stunting is a major global health issue, particularly in Indonesia, where malnutrition rates remain high. Poor childhood nutrition affects growth, cognition, and long-term health. Moringa oleifera is a nutrient-rich herbal supplement, but its nutritional composition varies by geography, potentially influencing its effectiveness in stunting interventions. Objective: To identify the best Moringa leaf source for extract production to support weight and height improvement in stunted children. Method: A systematic literature review (SLR) was conducted using Google Scholar, ScienceDirect, and PubMed (2014–2024). From 70 initially identified articles, 6 were selected using the PICOS method, focusing on Moringa supplementation, malnourished children, and growth outcomes. Results: Highland Moringa contains higher vitamin C and flavonoid levels, while lowland Moringa offers greater biomass for large-scale production. Studies confirm that dried Moringa extract significantly improves weight gain (p = 0.002), though its effects on height and inflammation reduction were less pronounced. Conclusion: Dried Moringa extract shows promise for weight gain and nutrition enhancement in stunted children. However, geographical factors influence its nutrient content, requiring further research to standardize formulations, optimize dosages, and assess long-term effects in human trials.